PHYTOCHEMICAL SCREENING OF FLOWERS OF COUROUPITA GUIANENSIS AUBL - Dr. Laxman Landge (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The phtocompounds that are found in the plants can scavenge free radicals are thus effective in ameliorating role in the progress of various types of diseases. Couroupita guianensis Aubl belonging to family Lecythidaceae is a common medicinal plant in India and South America, mainly it is used in Ayurvedic medicine as its antibiotic, antifungal, antiseptic, analgesic acitivities. To separate and characterize the phytocompounds from methanolic extract of Couroupita guianensis Aubl flowers using High Performance Liquid Chromatography – Mass Spectroscopy. The phytocompounds with retention times 12.323, 13.642, 14.926, 19.413 and 20.418 may be identified as swietenine, sapropterin, usnic acid, lupeol and gamma tocopherol (vit. E) Respectively by using HPLC-MS technique. According to HPLC-MS technology of methanolic extract of flowers of Couroupita guianensis Aubl, our study identified only limited number of phytocompounds.